The Effect of Physical Work Environment and Principal's Leadership on Teacher and Employee Performance - Supriyanto, Supriyanto; Purnomo, Eko; Susilawati, Dede; Sari, Cytra; Dasman, Sunita (Talent: Journal of Economics and Business, 2024)
This research aims to find out how the physical work environment and principal leadership influence the performance of teachers and employees in the world of education. The research objects were 59 teachers and employees at educational institutions. Data collection using a questionnaire via a Google Form link. Data processing uses the SmartPLS 3.0 statistical program. The results of the research show that the physical work environment and leadership of the school principal influence the performance of teachers and employees.